AUTOPSY REPORT ON THE FETAL DEATH OF A REVOLUTION: MEHÂ HASEN'S OMTI SABAHAN EYYETUHE'L-HARB NOVEL - Adnan ARSLAN (Fırat University, 2019)
In 2011, in Syria's Der'a province, the public protests that started in Hama and then leaped to other Syrian provinces in response to the children who had written against the Syrian regime on the walls were detained and tortured at the police station, turned into a bloody civil war within a few months. Many academic studies have been conducted on the political and military consequences of this civil war, which led to the death of tens of thousands of civilians and the abandonment of millions of people from that day to day. However, the results of the civil war are not limited to being political and military. Civil war; the fact that millions of Syrians have to migrate away from the war environment and have to migrate to safe areas in Syria or to neighboring countries outside of Syria have to face the consequential integration problem and that the same family members are involved in family disputes due to their different sides among the conflicting sectors and that some Syrians are especially against anti- then it became a social endeavor like the emergence of a part of the people who did not give support to any side and suffered a crisis of confidence, uncomfortable with the attitudes of the opponents. This study will address these social problems reflected in the Syrian novel writer Mehâ Hasen's novel Umti Sabahan Eyyetuhe'l-Harb and the background of failure of that revolution. In the introduction, information will be given on how the Syrian civil war started and developed from today. In the first chapter, the life and novelty of Mehâ Hasen will be mentioned. In the second chapter, the social problems caused by the civil war in Syria and the factors affecting the revolution’s failure will be discussed.